Efektivitas Lembaga Penjamin Simpanan (LPS) dalam Meningkatkan Kepercayaan Masyarakat Berdasarkan Tinjauan Yuridis dan Moral Hazard - Kesumadianty, Arnelia; Saragih, Desran JW; Marlianto, Dwi (Technology and Economics Law Journal, 2026)
This study examines the effectiveness of the Indonesia Deposit Insurance Corporation (LPS) in enhancing public trust in the stability of the Indonesian banking system and analyzes the potential moral hazard arising from the deposit insurance scheme. Employing a normative juridical method with a descriptive-analytical approach, the research reviews the legal framework of LPS under Law Number 24 of 2004 and its amendments, as well as Law Number 4 of 2023 on the Development and Strengthening of the Financial Sector (P2SK), and compares it with deposit insurance practices in several other jurisdictions. The findings indicate that LPS plays a crucial role as a financial safety net that strengthens depositor confidence, yet a deposit insurance design that is not sufficiently risk-based may encourage excessive risk-taking behavior by banks. The study recommends strengthening the implementation of risk-based premiums, enhancing prudential regulation and bank resolution frameworks, and improving corporate governance and risk management in order to mitigate moral hazard and safeguard financial system stability.